(untitled) (Journal of Educational Sciences, 2016)
At the present time due to changes in the socio-political situation in the society, development of the economyas a whole, the educational system is in need of expertise. In the given article are considered the subjects of the expert work in the area of education, the place and the role of the expert and his position in this area. Changes in the sphere of education in the time leading to the problem of increasing the quality of education. Indicator of the use of эспертизы in improving the quality of education is the need to satisfy the demands of обущающихся. The peculiarity of the application of expertise in scientific иследованиях is manifested in the purposes and tasks of the application. Expertise in the system of education is carried out by experts in accordance with the established нормамами and the standards of the examination. In General, the expert in the education system must comply with the mutual connection of the educational program and the subjects of expertise. In the article these issues are devoted to the different opinions expressed by authors in the field of examination, on the question of determination of subjects of expertise and methodological aspects of this problem. In the work of the субъектв expertise in the field of education considers the features of the subjective attitude. One of the main requirements for experts in the education system is the necessity of mastering practice of research and experimental works. About the effectiveness of the work of the expert says the application of innovative projects and software products. One of the factors of implementation of the function of experts in the field of education is the willingness of experts to cooperate with the administration, teachers, students and their parents. This is on the one hand to raise versatile information, on the other hand willingness to look with confidence to the decisions and instructions of the expert group. In addition, the authors расскрывают some approaches to the organization of the expert work, describe the main stages of expertise in education. In conclusion, offers suggestions for overcoming subjectivism in the expert process.